2016
DOI: 10.1111/gcbb.12302
|View full text |Cite
|
Sign up to set email alerts
|

Food and bioenergy: reviewing the potential of dual‐purpose wheat crops

Abstract: Within the bioenergy debate, the ‘food vs. fuel’ controversy quickly replaced enthusiasm for biofuels derived from first‐generation feedstocks. Second‐generation biofuels offer an opportunity to produce fuels from dedicated energy crops, waste materials or coproducts such as cereal straw. Wheat represents one of the most widely grown arable crops around the world, with wheat straw, a potential source of biofuel feedstock. Wheat straw currently has limited economic value; hence, wheat cultivars have been bred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 108 publications
(287 reference statements)
1
32
0
1
Order By: Relevance
“…However, our results showed no significant differences in grain yield, and therefore the higher straw biomass production was the main factor responsible for the higher CDM of landraces. Other studies have reported higher straw biomass production of landraces [28], which can have potential sustainability benefits. Cereal straw mulching has been proven to effectively reduce soil erosion and increase soil quality, biological activity, and soil aggregate stability [29] under Mediterranean rainfed conditions.…”
Section: Crop Dry Matter Grain Yield and Straw Biomassmentioning
confidence: 90%
“…However, our results showed no significant differences in grain yield, and therefore the higher straw biomass production was the main factor responsible for the higher CDM of landraces. Other studies have reported higher straw biomass production of landraces [28], which can have potential sustainability benefits. Cereal straw mulching has been proven to effectively reduce soil erosion and increase soil quality, biological activity, and soil aggregate stability [29] under Mediterranean rainfed conditions.…”
Section: Crop Dry Matter Grain Yield and Straw Biomassmentioning
confidence: 90%
“…This step is expected to increase liquid volume in the system, thus improving ethanol production rate by yeast [35,36]. In this study, the prehydrolysis times of 3,6, and 16 h were tested to find the suitable time for inoculating yeasts, and their ethanol yields were compared with that by the SSF alone ( Figure 6). The initial glucose concentrations increased according to increasing prehydrolysis time.…”
Section: Edx Analysismentioning
confidence: 99%
“…Rice straw (RS) is a by-product after rice grain collection. This lignocellulosic waste has been promoted as a potential feedstock for ethanol production in Thailand and other Asian countries due to its ready availability, abundance, and the fact that it is nonfood [3,4]. This material is an excellent source of sugars for microbial fermentation owing to the presence of carbohydrates that are concentrated in the cell walls [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to understanding farmers' willingness to supply straw from current production levels, farmers may also adjust their straw production practices in response to potentially higher straw prices resulting from changes in the straw market. Given that modern plant breeding and agronomic practice has led to production of shorter straw in cereal crops, Townsend et al (2015) reviewed the concept of a dual-purpose wheat cultivar that was optimised for grain for feed or food markets and straw for the biofuel market. Management practices that could influence straw yield were identified; however, given the lack of scientific focus towards increased straw production, there is little research to support these practices.…”
Section: Introductionmentioning
confidence: 99%